2000
DOI: 10.1136/bjo.84.9.1018
|View full text |Cite
|
Sign up to set email alerts
|

The second eye of Japanese patients with unilateral exudative age related macular degeneration

Abstract: Aim-To clarify the incidence of choroidal neovascularisation (CNV) and predisposing findings for development of CNV in the second eye of Japanese patients with unilateral exudative age related macular degeneration (AMD). Methods-The second eyes of unilaterally aVected patients with exudative (neovascular) AMD treated in our clinic during the past 10 years (1988-97) were carefully followed up for more than a year. Evidence of CNV was confirmed by fluorescein and indocyanine green angiography. Macular lesions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 17 publications
(20 reference statements)
1
24
0
Order By: Relevance
“…It has long been known that the prevalence of AMD varies widely among different ethnicities [Gregor and Joffe, 1978;Munoz et al, 2000;Oshima et al, 2001;Sommer et al, 1991;Eye Diseases Prevalence Research Group, 2004;Varma et al, 2004;Yuzawa et al, 1997]. Moreover, the phenotypic spectrum of AMD among these groups is quite heterogeneous [Andersen, 2004;Lim et al, 1998;Schachat et al, 1995;Sho et al, 2003;Uyama et al, 1992Uyama et al, , 2000Yuzawa et al, 1991].…”
Section: Introductionmentioning
confidence: 97%
“…It has long been known that the prevalence of AMD varies widely among different ethnicities [Gregor and Joffe, 1978;Munoz et al, 2000;Oshima et al, 2001;Sommer et al, 1991;Eye Diseases Prevalence Research Group, 2004;Varma et al, 2004;Yuzawa et al, 1997]. Moreover, the phenotypic spectrum of AMD among these groups is quite heterogeneous [Andersen, 2004;Lim et al, 1998;Schachat et al, 1995;Sho et al, 2003;Uyama et al, 1992Uyama et al, , 2000Yuzawa et al, 1991].…”
Section: Introductionmentioning
confidence: 97%
“…Data from the Asian population suggest a lower incidence of CNV in the second eye. 6,8,22 The MPS study has shown that characteristics of drusen and retinal pigmentary abnormalities are independent prognostic indicators for development of CNV. 15,16 These findings have been quantified in large population-based studies 1-3 and they provide a strong rationale for using these features to design a universally accepted grading system for stratifying ARM.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] However, soft drusen are not as prevalent in the Orientals. 22,24,28 In addition, the prevalence of retinal pigmentary changes is lower in the Orientals. 22 These findings contribute to the fact that the Chinese cohort has less ARM severity compared to Caucasians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japanese patients, Uyama et al [12] reported an incidence in the fellow eye of 12.3% over 5 years; Yuzawa et al [13] estimated incidences of 8% for 3 years, 12% for 5 years, and 20% for 10 years. These studies were conducted without the use of any anti-VEGF agents for the treatment of AMD.…”
Section: Discussionmentioning
confidence: 99%